Optimal Fasting Insulin Cutoff Value to Predict Clinical and/or Biochemical Hyperandrogenism in Korean Women with Polycystic Ovary Syndrome - Seula Lee; Hyeonjun An; Soojin Rhee; Sungwook Chun (IMR Press, 2023)
Background: Insulin resistance and compensatory hyperinsulinemia play a critical role in the development of hyperandrogenism (HA) in polycystic ovary syndrome (PCOS) patients. To the best of our knowledge, however, few studies have determined the optimal fasting insulin cutoff value to predict HA in PCOS patients. Through this study, we aimed to investigate the optimal cutoff values for insulin and homeostatic model assessment for insulin resistance (HOMA-IR) to predict HA in women with PCOS. Methods: One hundred forty-eight women whose menarche occurred over eight years ago and were newly diagnosed with PCOS with irregular menstrual cycles (IM) and polycystic ovaries (PCO) using ultrasound after ruling out other etiologies were enrolled in this study. In this study, participants were categorized into two groups: those with clinical or biochemical HA (the IM/PCO/HA group) and those without HA (the IM/PCO group). To assess the relationship between androgen levels, including total testosterone (TT) and free testosterone (FT), and fasting glucose and insulin levels and HOMA-IR values, we performed correlation analysis using Spearman's rank correlation coefficient. We used receiver operating characteristic (ROC) analysis to identify the optimal cutoff values for fasting insulin and HOMA-IR to predict HA in PCOS patients. Results: Fasting glucose and insulin levels and HOMA-IR values were significantly different between the IM/PCO/HA and IM/PCO groups. TT and FT levels exhibited significant correlations with fasting glucose and insulin levels and HOMA-IR values. The ROC analysis identified the most suitable fasting insulin cutoff value of 9.85 µU/mL with an area under the ROC curve (AUC) of 0.817 (60.7% sensitivity and 91.3% specificity) for predicting HA in women with PCOS. The ROC analysis also showed a HOMA-IR value of 2.22 as the optimal cutoff value for predicting HA (AUC, 0.820; 60.7% sensitivity, and 92.4% specificity). Conclusions: Our results support the classical concept that hyperinsulinemia contributes to HA in PCOS patients. Women with PCOS with fasting insulin levels of 9.85 µU/mL or higher (approximately ≥10 µU/mL) are strongly suspected to have HA.